Application Design ¨KoPiKu Kontrasepsi Pilihanku¨ of Mobile Contraception Decision Making Tools Based on Android - Meti Patimah; Ade Kurniawati; Sri Susilawati (JURNAL KEBIDANAN, 2020)
The use of contraception in Indonesia has not been maximized, based on data from the BKKBN new contraception participants chose to use the injection method. This is influenced by many factors, one of which is the knowledge and education level of women. Seeing the development of technology today is very rapid, so it is deemed necessary to develop an android-based contraceptive tool that is informative, educative, and applicable. The purpose of this research is to create a contraceptive guide application software that can be installed for mobile android that can be used by midwives and clients in increasing knowledge about contraceptive methods and makes it easy to determine suitable contraception as needed. The design of this application uses extreme software development that simplifies the various stages of the development process so that it becomes more adaptive and flexible. This research has succeeded in developing an application ‘KoPiKu¨ Kontrasepsi PilihanKu that can be used by midwives and clients, but still needs further development of features.